Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1016/0893-133x(95)00272-f
|View full text |Cite
|
Sign up to set email alerts
|

Can the Effects of Antidepressants Be Observed in the First Two Weeks of Treatment?

Abstract: Recently the claim that there is a lag in the time of onset of antidepressant effects has been questioned. This issue rests on contrasting the time course of ultimate responders versus nonresponders on imipramine and amitriptyline. It is concluded that in 1 week on antidepressants "clinicians were capable of detecting changes in general states between the groups and the specific effects of depressed mood and anxiety and the physical expression of distress" (Katz et al. 1987). To examine this issue, we first us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
2
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 13 publications
1
21
2
2
Order By: Relevance
“…More recently several authors reported that improvement observed after 1 week of treatment predicted patient response to clozapine [Stern et al, 1994] and haloperidol [Harvey et al, 1991;Stern et al, 1993]. Similar findings are evident in the depression literature [Coryell et al, 1982;Mitchell et al, 2000;Nierenberg et al, 1995Nierenberg et al, , 2000Quitkin et al, 1996;Szegedi et al, 2003]. Nierenberg et al [1995], for example, reported that more than half of all fluoxetine responders [defined as a change 450% in the Hamilton Depression Scale (HAM-D)] at 8 weeks had already responded by week 2, and the authors concluded that nonresponse to treatment as early as week 2 predicts 8-week outcome.…”
Section: Introductionmentioning
confidence: 59%
“…More recently several authors reported that improvement observed after 1 week of treatment predicted patient response to clozapine [Stern et al, 1994] and haloperidol [Harvey et al, 1991;Stern et al, 1993]. Similar findings are evident in the depression literature [Coryell et al, 1982;Mitchell et al, 2000;Nierenberg et al, 1995Nierenberg et al, , 2000Quitkin et al, 1996;Szegedi et al, 2003]. Nierenberg et al [1995], for example, reported that more than half of all fluoxetine responders [defined as a change 450% in the Hamilton Depression Scale (HAM-D)] at 8 weeks had already responded by week 2, and the authors concluded that nonresponse to treatment as early as week 2 predicts 8-week outcome.…”
Section: Introductionmentioning
confidence: 59%
“…This placebo response has been linked to poorer long-term outcomes, particularly relapse during follow-up of patients treated with antidepressant medications. Several studies have investigated this possibility and support the contention that a "premature" drug response (one that occurs before a therapeutic dose has been administered) foretells poor longterm therapeutic outcomes (Quitkin, McGrath, Stewart, Taylor, & Klein, 1996;Quitkin et al, 1987;Quitkin, Rabkin, Ross, & McGrath, 1984;Stewart et al, 1998). Few studies have investigated the timing of response in psychotherapy with the intent of understanding the active ingredients of treatment and the place of common and unique therapeutic factors.…”
Section: Early Treatment Response-another Challenge To Theory-specifimentioning
confidence: 99%
“…Several studies have investigated this possibility and support the contention that a premature drug response foretells poor long-term therapeutic outcomes (Quitkin, Rabkin, Ross, & McGrath, 1984;Quitkin et al, 1987;Quitkin, McGrath, Stewart, Taylor, & Klein, 1996;Stewart et al, 1998).…”
mentioning
confidence: 96%